Acute systemic myeloid inflammatory and stress response in severe food allergic reactions - Sharma, Ankit; Rijavec, Matija; Tomar, Sunil; Yamani, Amnah; Ganesan, Varsha; Krempski, James; Schuler, Charles F.; Bunyavanich, Supinda; Korosec, Peter; Hogan, Simon P. (Clinical and experimental allergy, 2023)
Introduction Food allergic reactions can be severe and potentially life‐threatening and the underlying immunological processes that contribute to the severity of reactions are poorly understood. The aim of this study is to integrate bulk RNA‐sequencing of human and mouse peripheral blood mononuclear cells during food allergic reactions and in vivo mouse models of food allergy to identify dysregulated immunological processes associated with severe food allergic reactions. Methods Bulk transcriptomics of whole blood from human and mouse following food allergic reactions combined with integrative differential expressed gene bivariate and module eigengene network analyses to identify the whole blood transcriptome associated with food allergy severity. In vivo validation immune cell and gene expression in mice following IgE‐mediated reaction. Results Bulk transcriptomics of whole blood from mice with different severity of food allergy identified gene ontology (GO) biological processes associated with innate and inflammatory immune responses, dysregulation of MAPK and NFkB signalling and identified 429 genes that correlated with reaction severity. Utilizing two independent human cohorts, we identified 335 genes that correlated with severity of peanut‐induced food allergic reactions. Mapping mouse food allergy severity transcriptome onto the human transcriptome revealed 11 genes significantly dysregulated and correlated with severity. Analyses of whole blood from mice undergoing an IgE‐mediated reaction revealed a rapid change in blood leukocytes particularly inflammatory monocytes (Ly6Chi Ly6G−) and neutrophils that was associated with changes in CLEC4E, CD218A and GPR27 surface expression. Conclusions Collectively, IgE‐mediated food allergy severity is associated with a rapid innate inflammatory response associated with acute cellular stress processes and dysregulation of peripheral blood inflammatory myeloid cell frequencies.